2016
DOI: 10.1016/j.mrfmmm.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Extreme dNTP pool changes and hypermutability in dcd ndk strains

Abstract: SUMMARY Cells lacking deoxycytidine deaminase (DCD) have been shown to have imbalances in the normal dNTP pools that lead to multiple phenotypes, including increased mutagenesis, increased sensitivity to oxidizing agents, and to a number of antibiotics. In particular, there is an increased dCTP pool, often accompanied by a decreased dTTP pool. In the work presented here, we show that double mutants of E. coli lacking both DCD and NDK (nucleoside diphosphate kinase) have even more extreme imbalances of dNTPs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…4 is similar to the respective figure we constructed for DCD-deficient cells (61). The spectrum of rpoB mutations in the 2AP plus ZEB com- bination does share one hot spot with the spectra of DCD-, NDK-, or DCD-and NDK-deficient strains, the A·T¡G·C mutation at position 1547 (36,41,42), although this site also represents a hot spot for spontaneous mutations in either a wild-type or mismatch repair-deficient background (35,39). What really stands out in Fig.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…4 is similar to the respective figure we constructed for DCD-deficient cells (61). The spectrum of rpoB mutations in the 2AP plus ZEB com- bination does share one hot spot with the spectra of DCD-, NDK-, or DCD-and NDK-deficient strains, the A·T¡G·C mutation at position 1547 (36,41,42), although this site also represents a hot spot for spontaneous mutations in either a wild-type or mismatch repair-deficient background (35,39). What really stands out in Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Long-standing work in both microbial and mammalian cells has shown that alterations of the dNTP pools can affect mutation rates (31,41,42,44,(50)(51)(52)(53)(54). More recently, studies in E. coli have shown that perturbations in the absolute levels of all four dNTPs, even when the ratios are not altered, leads to changes in mutation rates (26,55,56).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations